2012
DOI: 10.1007/s00213-012-2959-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of spinal 5-HT1A receptors in isolation rearing-induced hypoalgesia in mice

Abstract: These findings suggest that isolation rearing causes hypoalgesia in mouse models of acute pain and imply that the spinal 5-HT1A receptor activation probably through descending serotonergic inhibitory pathway is involved in isolation rearing-induced hypoalgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
2
10
1
Order By: Relevance
“…The delayed recognition of acute illnesses and/or failure to respond to pain cues results in increased morbidity and mortality in patients with schizophrenia. Consistent with the clinical reports, social isolation rearing in mice after weaning reduces pain sensitivity to acute thermal and chemical (acetic acid and capsaicin) noxious stimuli (27) and inhibits FCA-induced mechanical allodynia (28). Regarding the underlying mechanisms, we have demonstrated that isolation rearing causes neuronal activation of the anterior cingulate cortex, periaqueductal gray matter, and rostral ventromedial medulla, but not the locus coeruleus, in mice and that intrathecal injection of WAY100635 alleviated hypoalgesia in capsaicin-induced nociception and inhibition of mechanical allodynia in isolation-reared mice (27,28).…”
Section: Hypoalgesiasupporting
confidence: 84%
See 2 more Smart Citations
“…The delayed recognition of acute illnesses and/or failure to respond to pain cues results in increased morbidity and mortality in patients with schizophrenia. Consistent with the clinical reports, social isolation rearing in mice after weaning reduces pain sensitivity to acute thermal and chemical (acetic acid and capsaicin) noxious stimuli (27) and inhibits FCA-induced mechanical allodynia (28). Regarding the underlying mechanisms, we have demonstrated that isolation rearing causes neuronal activation of the anterior cingulate cortex, periaqueductal gray matter, and rostral ventromedial medulla, but not the locus coeruleus, in mice and that intrathecal injection of WAY100635 alleviated hypoalgesia in capsaicin-induced nociception and inhibition of mechanical allodynia in isolation-reared mice (27,28).…”
Section: Hypoalgesiasupporting
confidence: 84%
“…Consistent with the clinical reports, social isolation rearing in mice after weaning reduces pain sensitivity to acute thermal and chemical (acetic acid and capsaicin) noxious stimuli (27) and inhibits FCA-induced mechanical allodynia (28). Regarding the underlying mechanisms, we have demonstrated that isolation rearing causes neuronal activation of the anterior cingulate cortex, periaqueductal gray matter, and rostral ventromedial medulla, but not the locus coeruleus, in mice and that intrathecal injection of WAY100635 alleviated hypoalgesia in capsaicin-induced nociception and inhibition of mechanical allodynia in isolation-reared mice (27,28). These findings suggest that the spinal 5-HT 1A receptor activation via the descending serotonergic inhibitory pathway contributes to isolation rearing-induced hypoalgesia and reduced pain sensitivity to tactile stimulation under conditions of chronic inflammatory pain (Fig.…”
Section: Hypoalgesiasupporting
confidence: 84%
See 1 more Smart Citation
“…Ethanol directly activates the transient receptor potential vanilloid 1 (TRPV1), a heat-gated nociceptor also activated by spicy foods containing capsaicin (Trevisani et al 2002), which induces an aversive/painful burning sensation in the mouth and the periphery. Mice reared in isolation have impaired TRPV1 nociception across multiple measures compared to group-reared controls (Horiguchi et al 2013). Reduction in temperature-related pain sensitivity is also found in isolated rats (Petrovszki et al 2013).…”
Section: Discussionmentioning
confidence: 93%
“…The MS protocol was performed for 2 hours (from 8 a.m. to 10 a.m.) from PND 12 until PND 21. The litters were removed from dams and placed in separate cages, somatosensory cortex and anterior cingulate cortex, has the potential to cause alterations in pain behavior (5,6). Cytoarchitecture changes in somatosensory areas are also associated with nociceptive sensitivity and chronic pain conditions (7).…”
Section: Ms Groupmentioning
confidence: 99%